2009
DOI: 10.1097/aud.0b013e3181b1354f
|View full text |Cite
|
Sign up to set email alerts
|

Auditory N1 Component to Gaps in Continuous Narrowband Noises

Abstract: The auditory N1 component can be recorded to gaps in continuous narrowband noises whose gap thresholds are grossly similar to those obtained psychophysically. The differences found between PGTs and EGTs with different narrowband noise center frequencies call for further investigation of narrowband noise stimuli for the study of temporal resolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
30
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 43 publications
7
30
0
Order By: Relevance
“…Comparison of the time-course of this component with the audio envelope shows that the correlation between them is quite high for some stimuli, but quite low for some others. The most obvious difference between these stimuli appears to be the event density in the music, however other factors could also be of influence, such as the bandwidth of the signal, as was reported by Atcherson et al (2009). Exploring a possible relation with music structure we found the strongest correlation lags between the EEG and different musical events differed over stimuli as well, supporting the notion that different processes are contributing to the brain signal that is useful for the detection of the representation.…”
Section: Discussionsupporting
confidence: 78%
“…Comparison of the time-course of this component with the audio envelope shows that the correlation between them is quite high for some stimuli, but quite low for some others. The most obvious difference between these stimuli appears to be the event density in the music, however other factors could also be of influence, such as the bandwidth of the signal, as was reported by Atcherson et al (2009). Exploring a possible relation with music structure we found the strongest correlation lags between the EEG and different musical events differed over stimuli as well, supporting the notion that different processes are contributing to the brain signal that is useful for the detection of the representation.…”
Section: Discussionsupporting
confidence: 78%
“…Source-modelling showed that the gap-evoked response originates in planum temporale, just posterior to primary auditory cortex, similar to the source of other auditory responses such as the N1 evoked by sound onset. Consistent with previous reports (e.g., Atcherson et al, 2009;Michalewski et al, 2005;Pratt et al, 2005Pratt et al, , 2007, the responses to gaps in noise were time-locked to the offset of noise at the start of the gap, rather than the noise-onset at the end of the gap (Fig. 1D).…”
Section: Morphology and Spatial Distribution Of Gap-evoked Responsessupporting
confidence: 89%
“…The average latency for this initial response was 90 ms (SD 15 ms) in the left hemisphere and 88 ms (SD 15 ms) in the right hemisphere, with no significant latency difference between the hemispheres. This response is similar to the "N1" response to gaps reported by some previous authors (Atcherson et al, 2009;Harris et al, 2012;Lister et al, 2011a). Other studies have reported that the response to gaps in noise consists of a bifid peak (Michalewski et al, 2005;Pratt et al, 2005Pratt et al, , 2007 and the absence of the earlier component here is likely due to the windowing of the gaps in our stimulus, which reduces spectral splatter associated with the offset of noise.…”
Section: Spatio-temporal Distribution Of Evoked Responsessupporting
confidence: 87%
See 2 more Smart Citations